About the subjective scope of labour law from the perspective work-life balance concept - Pietras, Aleksandra (Acta Universitatis Lodziensis. Folia Iuridica, 2019)
In Poland, a significant number of people employed on a legal basis other than the employment relationship, carry out work in the conditions of economic dependence. On the other hand, there is a departure from the classical model of employee subordination, which is connected with greater independence of employees and is a consequence of the development of atypical forms of employment also within the employment relationship. Taking this into account, it is worth considering how the subjective scope of labour law should be shaped in the future. The social standing of all people for whom work is the basic source of income, and therefore the condition of a good life, is more and more similar, and negative consequences of conflicts between the sphere of professional and private life are equally severe regardless of the legal basis of employment. The social interest therefore requires taking into account some threats accompanying various forms of work done.